2020
DOI: 10.1051/0004-6361/201936492
|View full text |Cite
|
Sign up to set email alerts
|

Ceres observed at low phase angles by VIR-Dawn

Abstract: Context. Particulate surfaces exhibit a surge of reflectance at low phase angles, a phenomenon referred to as the opposition effect (OE). Two mechanisms are recognized as responsible for the OE: shadow hiding (SH) and coherent backscattering. The latter is typically characterized by a small angular width of a few degrees at most and according to the theoretical prediction should exhibit wavelength and albedo dependence. Aims. We characterize the OE on the surface of Ceres using Dawn Visible InfraRed mapping sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The phase reddening coefficient determined for the Wosret region is comparable to the one found for other dark and presumed organic rich bodied such as D-type asteroids (0.05 ± 0.03 × 10 −4 nm −1 deg −1 in the 0.45-2.45 µm range, Lantz et al 2017), and the dwarf planet Ceres (γ = 0.046 × 10 −4 nm −1 deg −1 , Ciarniello et al 2017Ciarniello et al , 2020. It is however two to four times higher than the value reported for low albedo and carbonaceous rich bodies such as the near-Earth asteroids: (101955) Bennu and ( 162173) Ryugu (Table 2), that were recently visited by the OSIRIS-REx and Hayabusa 2 missions, respectively.…”
Section: Spectral Phase Reddeningsupporting
confidence: 78%
“…The phase reddening coefficient determined for the Wosret region is comparable to the one found for other dark and presumed organic rich bodied such as D-type asteroids (0.05 ± 0.03 × 10 −4 nm −1 deg −1 in the 0.45-2.45 µm range, Lantz et al 2017), and the dwarf planet Ceres (γ = 0.046 × 10 −4 nm −1 deg −1 , Ciarniello et al 2017Ciarniello et al , 2020. It is however two to four times higher than the value reported for low albedo and carbonaceous rich bodies such as the near-Earth asteroids: (101955) Bennu and ( 162173) Ryugu (Table 2), that were recently visited by the OSIRIS-REx and Hayabusa 2 missions, respectively.…”
Section: Spectral Phase Reddeningsupporting
confidence: 78%
“…Thus, we assumed p = 1 in the absence of further constraints. We note that analysis of VIR data obtained for different phase angles showed that the SPPF of Ceres' averaged surface is fairly symmetric in IR (Ciarniello et al., 2017, 2020).…”
Section: Methodsmentioning
confidence: 76%
“…Assumption of isotropic scattering in our model may underestimate the darkening effect of magnetite due to its forward scattering (Mustard & Pieters, 1989). However, analysis of Ceres' photometric properties (Ciarniello et al., 2017, 2020) showed back scattering or symmetrical scattering, depending on different assumptions, which suggests that strong forward scattering is unlikely to be a major cause of Ceres' low albedo.…”
Section: Discussionmentioning
confidence: 99%
“…For the dwarf planet Ceres, Ciarniello et al (2017Ciarniello et al ( , 2020) reported a monotonic spectral phase reddening throughout visible to NIR wavelengths, with γ values of 0.0046 µm −1 deg −1 in the 0.55-0.8 µm range and 0.0015 µm −1 deg −1 in the 1.2-2 µm range. Thus phase reddening is progressively less sensitive to wavelength in the IR, that is, it gets smaller at longer wavelengths.…”
Section: Discussionmentioning
confidence: 99%